Systematic Literature Review of Early Estrogen Exposure and its Relation to Breast Cancer in Woman - Ni Putu Manik Suryaningsih; Pratika Yuhyi Hernanda; Roethmia Yaniari (Universitas Wijaya Kusuma Surabaya, 2023)
Breast cancer cell begins in the ductal epithelium and its lobes, where abnormal cell growth that is excessive, uncoordinated, and susceptible to metastasis accumulates. This study set out to find out how far early estrogen exposure influence the risk of having breast cancer in women. This systematic literature review was done by collecting sources related to the investigated variables which are menarche age, age at first birth and hormonal contraception use. We collect from variety of sources such as Google Scholar, PubMed, and Proquest to draw conclusions by grouping the odds ratio (OR) and their 95% CI. Data of the research articles, including author, year, title, and research results in the form of p-value, OR, and 95% CI, were collected from 35 articles published between 2011 and 2022 for this study. The data analysis revealed woman with menarche age at less than 12 years old have more likely to have breast cancer (range of OR 0.80 – 26.8), meanwhile woman who give birth more than 30 years old also have more likely to have breast cancer ( range of OR 1.26 – 6.47) and duration of hormonal contraception use > 5 years were also give more chance to breast cancer development (range OR 0.51 – 9.06). This review analysis highlighted the increased probability in the incidence of breast cancer in woman related to the duration of hormonal contraception use, the age of menarche, and the age at first birth.